Pengaruh Kecerdasan Buatan (Artificial Intelligent) pada Adopsi Teknologi dalam Praktik Akuntansi di Indonesia - Marsha Nisa A. Yusuf; Dr. Regina J. Arsjah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the influence of technology readiness, perceived usefulness, and perceived ease of use on the adoption of artificial intelligence (AI) technology among professional accountants in Indonesia. Using the Technology Rediness Acceptance Model (TRAM), this study involved 101 accountant respondents. The analysis results show that all three variables significantly influence the adoption of AI. However, age was not proven to be a significant moderator in this relationship. These findings indicate that internal organizational factors, such as technology readiness and perceptions of the benefits of AI, are more dominant in driving adoption than demographic factors such as age. This study suggests the importance of developing comprehensive training programs to improve accountants' technology readiness and accelerate the adoption of AI in the accounting industry.